Agentes da morte: o ato da leitura nas obras O matador, de Wander Piroli e Odilon Moraes, e Nós matamos o cão Tinhoso, de Luís Bernardo Honwana - Souza, Mariane Rodrigues de (2021)
This research aims to analyze the narratives O Matador, by Wander Piroli and Odilon Moraes, and Nós matamos o Cão Tinhoso, by Luís Bernardo Honwana, in view of the reverberations that they reach from the internal and external construction of their narrators as agents of death. It is also the focus of this journey to show how the complexity of the theme is in contiguity with elements that build the narratives, establishing a difference between the information that is initially granted and the understanding achieved by the act of reading. We adopt as a hypothesis that in the analyzed works there are elements marked by repetition, which at each moment resignify themselves in a relationship of closeness and distance in terms of the awareness of the acts committed by the narrators, that results in the reader's experience with the work. We bring a new excerpt on the works of the analyzed corpus and on the research on the theme of death in the literature aimed at young people. We follow trends that treat literature for young people as equivalent to literature for adults as to the power that resides in it. For this, we base our evidence on María Teresa Andruetto, Marisa Lajolo, Regina Zilberman and Peter Hunt. Still on the clipping of the audience to which a work is directed, we also rely on Pierre Bourdieu. On how the theme of death appears in the corpus works, we reflect from Maria Júlia Kovács and Teresa Colomer. As for the narrative construction that takes place between the work and the reader, we take Wolfgang Iser, Gilles Deleuze, Félix Guattari, Walter Benjamin, Roland Barthes, Suzy Lee, Maria Nikolajeva, Carole Scott and Sophie Van der Linden as main references; the last three for studies on images. We hope to expand the space for reading and discussing narratives that bring discomfort necessary for reflections that reverberate in life itself